Penerapan Sanksi Administratif Sebagai Sarana Pengendali Pembatasan Terhadap Kebebasan Bertindak Bagi Notaris - Bahder Johan Nasution (Magister Kenotariatan, Universitas Jambi, 2020)
The application of administrative sanctions against violations of a license to practice or work issuing a deed outside the area of placement of the work area for a notary as a controlling suggestion in a permit is a limitation on the freedom to act. Permission is interpreted as an exception to everything that is in principle prohibited or prohibited, so the granting of a permit is an exception to the prohibition. Permission as a legal instrument in limiting freedom of action for a person must rely on the rule of law and general principles of good governance. The application of administrative sanctions in a permit functions to regulate, control and or direct one's freedom of action to act in accordance with the rule of law.